1976
DOI: 10.1017/s0043174500066078
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Thiocarbamate Injury to Corn II. Soil Incorporation, Seed Placement, Cultivar, Leaching, and Breakdown

Abstract: The influence of several factors on the injury to corn (Zea maysL.) seedlings from high rates of EPTC (S-ethyl dipropylthiocarbamate) + R-25788 (N,N-diallyl-2,2-dichloroacetamide) was determined in growth chambers. This herbicide combination severely injured 6% of the corn seedlings at rates as low as 14 ppm if the herbicide was poorly incorporated into the soil. If thoroughly incorporated, severe injury did not occur unless the rate of application exceeded 56 ppm. Decreased injury resulted when seed were plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 4 publications
0
17
0
1
Order By: Relevance
“…A performance do dichlormid pode ser afetada pelo método de incorporação ao solo, assim como pela forma em que a semente é tratada, tipo de equipamento utilizado na semeadura e comportamento do herbicida a ser utilizado (Burt, 1976). Nesse sentido, Burt & Buzio (1980) mencionaram diferença no grau de solubilidade entre o EPTC e o dichlormid causada pela lixiviação dos dois componentes com remoção das substâncias químicas da zona tratada em diferentes proporções na presença de chuvas pesadas ou irrigação, causando danos às plantas cultivadas (sorgo e arroz) e protegendo as plantas daninhas do efeito herbicida.…”
Section: Limitações De Usos De Safeners Como Protetores Químicosunclassified
“…A performance do dichlormid pode ser afetada pelo método de incorporação ao solo, assim como pela forma em que a semente é tratada, tipo de equipamento utilizado na semeadura e comportamento do herbicida a ser utilizado (Burt, 1976). Nesse sentido, Burt & Buzio (1980) mencionaram diferença no grau de solubilidade entre o EPTC e o dichlormid causada pela lixiviação dos dois componentes com remoção das substâncias químicas da zona tratada em diferentes proporções na presença de chuvas pesadas ou irrigação, causando danos às plantas cultivadas (sorgo e arroz) e protegendo as plantas daninhas do efeito herbicida.…”
Section: Limitações De Usos De Safeners Como Protetores Químicosunclassified
“…EPTC and R-25788 are known to decompose in the soil at similar rates (3,17). In time, however, they may become separated in the soil profile because R-25788 moves more readily during leaching or drying (3,6,17). Thomas and Gray (17) found that the half-life of R-25788 at 27 C was 8 days in Sorrento loam and 9 days in Felton loamy sand.…”
Section: Introductionmentioning
confidence: 99%
“…Dent corn inbreds were most susceptible to EPTC even when R-25788 was present. Dif ferences in response to EPTC treatment were thought to be due to genetic variation 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Alachlor, EPTC + R-25788, and vernolate + R-25788 usually control weeds selectively in sweetcorn (12,13); however, these herbicides occasionally injure the crop (1,2,4,5,6,14,18). R-25788 is a physiologically selective anti dote that protects corn from thiocarbamate herbicides under most conditions (9).…”
Section: Introductionmentioning
confidence: 99%